Investigation on Complementary Medicine Intervention in Breast Cancer Patients with Pain - Tacón, A. M. (New Frontiers in Medicine and Medical Research Vol. 7, 2021)
Aims: The purpose here was to newly investigate a five-weeks complementary medicine intervention, mindfulness-based intervention (MBSR), in breast cancer patients with chronic pain. Pain is the most persistent and incapacitating symptom experienced by cancer patients. Psychological pain inflexibility, pain self-efficacy, and expressive suppression were investigated for the first time in breast cancer patients with cancer-related pain. Study Design: One group pre-post intervention design. Place and Duration of Study: Lubbock, Tx medical center, spring 2010. Methodology: Sample: The sample consisted of 46 participants with 36 women in stage II (78%) and 10 (22%) in stage III with a mean age of 55 years. The MBSR intervention was held in a hospital counseling center for 1.5 hours/week for eight-weeks, with preliminary data collected at five weeks (reported here), at the end of the full program three weeks later, and three months post the 8-week program. Preliminary data here were collected on standardized instruments before (pre) and after (post) the five-week point of the eight-week MBSR program to evaluate intervention effects on the following: Psychological inflexibility in pain, pain self-efficacy, emotional regulation of suppressive expression, and pain intensity. Results: Psychological inflexibility in pain scores prior to the program (M=60.05, SD=14.22) decreased significantly by the end of five-weeks of the program (M=57.68, SD=13.46) (t=3.76, P = 0.01); Pain self-efficacy prior to the program (M=20.61, SD=11.47) increased significantly by the end of the five-week period of the complementary mindfulness intervention (M=22.47, SD=10.63) (t=3.11, P < 0.05); Emotional regulation strategy of suppression before the program (M=22.77, SD=7.75) dropped significantly by the end of the five-week mark (M=19.63, SD=8.43) (t=3.68, P = 0.01); lastly, pain intensity prior to the beginning of the intervention (M=33.67, SD=8.48) did not change significantly by the end of the five-week mark (M=32.86, SD=8.20) (P > .05). Conclusion: These findings after the complementary mindfulness intervention should be interpreted cautiously, for replication and future research need to be conducted at this time period. The results, however, provide data for women with breast cancer-related pain and the possibility of complementary mind-body interventions.